Pengaruh Populasi, Upah Minimum, dan Human Capital Terhadap Pengangguran Terbuka di Provinsi Lampung: Perspektif Ekonomi Islam - Safitri, Adelia; Fuadi, Fatih; Ermawati, Liya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
This study aims to analyze the influence of population, provincial minimum wage, and human capital on the open unemployment rate in Lampung Province in 2018-2024 from an Islamic economic perspective. The data used are panel data sourced from the Central Statistics Agency (BPS), and analyzed using a quantitative approach with the Fixed Effect Model (FEM) method through EViews 10 software. Based on the results of the t-test in this study, it shows that partially the population has a negative and significant effect on the open unemployment rate in Lampung Province, with a coefficient value of -0.057919 and a probability of 0.0011 (< 0.05). The provincial minimum wage also has a negative and significant effect on the open unemployment rate in Lampung Province, with a coefficient value of -3.121572 and a probability of 0.0032 (< 0.05). Meanwhile, human capital as measured by the human development index does not have a significant effect on the open unemployment rate in Lampung Province with a coefficient of 3.972250 and a probability of 0.3727 (> 0.05). Simultaneously, population, provincial minimum wage, and human capital significantly influence the open unemployment rate in Lampung Province with an f-statistic value of 7.804487 and a probability of 0.0000 (< 0.05). From an Islamic economic perspective, efforts to overcome unemployment should not only focus on achieving economic indicators alone, but must also be supported by principles of social justice such as equal employment opportunities and skills training to create jobs and empower communities sustainably.